Ethnic Pork Curry Products of Assam: Production Process, Quality and Storage Stability - P. S., Girish; Deori, Meetali; Bora, Mondira; Nath, Lipika; Barman, Keshab; Banik, S. (Journal of Meat Science, 2019)
Curry products are ethnic spicy Indian food products prepared with meat, vegetables, spices, condiments etc. Different curry products prepared from pork, traditionally in Assam state of North Eastern India have been documented in this study. Formulation and procedure followed for preparation of five pork curry products viz., pork - thekera tenga curry, pork - fermented bamboo shoot curry, pork - el ephant apple curry, pork - banana flower curry and pork - banana stem curry was gathered by undertaking survey and interacting with local processors of the region. These products were analyzed for standard quality parameters like physicochemical characteristics, mi crobiological quality and sensory acceptability. Storage stability of the products under aerobic refrigeration (4±1 ºC) was also evaluated. Products were stable up to 20 days of storage under aerobic refrigeration condition. The study revealed that ingredients used in curry preparation like thekera tenga, fermented bamboo shoot and elephant apple contribute significantly to sensory attributes and also help in enhancing storage stability of the pork curry products.